2012
DOI: 10.1186/1756-0500-5-194
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements as tumor biomarkers and prognostic factors in breast cancer: a study through energy dispersive x-ray fluorescence

Abstract: BackgroundThe application and better understanding of traditional and new breast tumor biomarkers and prognostic factors are increasing due to the fact that they are able to identify individuals at high risk of breast cancer, who may benefit from preventive interventions. Also, biomarkers can make possible for physicians to design an individualized treatment for each patient. Previous studies showed that trace elements (TEs) determined by X-Ray Fluorescence (XRF) techniques are found in significantly higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 64 publications
1
39
0
4
Order By: Relevance
“…Therefore, this element can comprise a double function: Iron deficiency can speed up tumor growth because of angiogenesis activation, whereas its excess can promote the transformation of normal cells into neoplastic cells by inducing oxidative stress. [40,46] clinicopathological data are on Silva et al [13] Figure 7(a and b) shows that the negative expression of iron occurs most often in young and premenopausal women, probably because of the fact that the systemic iron concentration is lower in women under these conditions. [47] Figure 7(a) also shows that the positive expression of Fe is higher in older women, probably because of the accumulation of this element in the organism due to menopause.…”
Section: Calcium and Zincmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, this element can comprise a double function: Iron deficiency can speed up tumor growth because of angiogenesis activation, whereas its excess can promote the transformation of normal cells into neoplastic cells by inducing oxidative stress. [40,46] clinicopathological data are on Silva et al [13] Figure 7(a and b) shows that the negative expression of iron occurs most often in young and premenopausal women, probably because of the fact that the systemic iron concentration is lower in women under these conditions. [47] Figure 7(a) also shows that the positive expression of Fe is higher in older women, probably because of the accumulation of this element in the organism due to menopause.…”
Section: Calcium and Zincmentioning
confidence: 93%
“…For example, if Ca concentration was above 212.6 mg/kg, the tissue can be classified as malignant. See reference Silva et al [13] On the basis of the cut-off values, trace element expression was determined. If the trace element concentration in a tissue was above the cut-off point, the trace element expression in that tissue was considered positive, and if trace element concentration in a tissue was below the cut-off point, then the trace element expression in that tissue was considered negative.…”
Section: Expression Of Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, research by Silva et al (9) showed that concentrations of trace elements are higher in neoplastic tissues (malignant and benign) when compared with normal tissues. Thus, there is still inconsistency of research results on the effect of trace element level on breast cancer.…”
Section: Introductionmentioning
confidence: 97%